2011
DOI: 10.1016/j.dsr2.2010.10.015
|View full text |Cite
|
Sign up to set email alerts
|

The SOLAS air–sea gas exchange experiment (SAGE) 2004

Abstract: 1The SOLAS air-sea gas exchange experiment (SAGE) was a multiple-objective study investigating 2 gas-transfer processes and the influence of iron fertilisation on biologically driven gas exchange in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…Nevertheless, our results agree with those of SAZ‐SENSE, which reported lower export and greater mesopelagic remineralization in naturally iron‐replete than in iron‐limited low‐Si sub‐Antarctic waters [ Bowie et al ., ; Ebersbach et al ., ; Jacquet et al ., ]. Only a modest response, mostly by nondiatom phytoplankton <20 µm, was found upon iron fertilization of sub‐Antarctic low‐Si waters during SAGE, suggesting that export was probably not greatly enhanced [ Harvey et al ., ; Peloquin et al ., ]. In contrast, POC export at the low‐Si sub‐Antarctic SOFeX North site was enhanced by iron fertilization, with NO 3 − depletion similar to LOHAFEX [ Bishop et al ., ; Coale et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our results agree with those of SAZ‐SENSE, which reported lower export and greater mesopelagic remineralization in naturally iron‐replete than in iron‐limited low‐Si sub‐Antarctic waters [ Bowie et al ., ; Ebersbach et al ., ; Jacquet et al ., ]. Only a modest response, mostly by nondiatom phytoplankton <20 µm, was found upon iron fertilization of sub‐Antarctic low‐Si waters during SAGE, suggesting that export was probably not greatly enhanced [ Harvey et al ., ; Peloquin et al ., ]. In contrast, POC export at the low‐Si sub‐Antarctic SOFeX North site was enhanced by iron fertilization, with NO 3 − depletion similar to LOHAFEX [ Bishop et al ., ; Coale et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Only two FeAXs were conducted in low‐silicon (Si) waters (Southern Ocean iron enrichment experiment (SOFeX) North and SOLAS air‐sea gas exchange experiment (SAGE)). However, diatoms were abundant and, apparently, not Si limited during SOFeX North [ Coale et al ., ], while downward particle export was not measured during SAGE [ Harvey et al ., ]. Recent work has suggested that Fe supply to low‐Si Southern Ocean regions may not enhance POC flux, although appreciable POC flux occurs there naturally [ Bowie et al ., ; Henson et al ., ; Trull et al ., ].…”
Section: Introductionmentioning
confidence: 98%
“…Here, wind, waves and currents develop unhindered by land, and strong persistent westerlies act over long fetch to generate large swells that propagate northeast influencing the wave climate off New Zealand. While this wave energy is attenuated closer to land in the eastern Chatham Rise, the average wave energy is still 75 % of values south of New Zealand, where annual mean wave heights exceed 4 m. Subantarctic waters south of the Chatham Rise region provided a prime location for a dual tracer release experiment (SAGE; Harvey et al, 2011), aimed at constraining k at high wind speeds. Comparison of the SAGE k-wind-speed parameterization with those generated in other regions and using different techniques showed generally good agreement (Ho et al, 2006); this may be interpreted as indicating that regional influences on exchange may be less important, supporting the application of a universal wind speed parameterization.…”
Section: Regional Contextmentioning
confidence: 99%
“…To test the effects of iron fertilization on marine ecosystems and carbon cycle in actual ocean areas, a number of field experiments have been performed in the HNLC waters in the eastern equatorial Pacific [ Coale et al , 1996] and the subarctic North Pacific Ocean [ Tsuda et al , 2003; Boyd et al , 2004; Law et al , 2006; Wong et al , 2006]. The Southern Ocean has been the site of several fertilization experiments as well, in the Atlantic [ Bakker et al , 2001], Indian [ Boyd et al , 2000; Boyd and Law , 2001; Gervais et al , 2002], and Pacific sectors [ Coale et al , 2004; Harvey et al , 2011]. All but the SOLAS Air‐Sea Gas Exchange Experiment (SAGE) [ Harvey et al , 2011] southeast of New Zealand showed strong increases in the primary productivity and biomass in mixed layer, and depletion of dissolved inorganic carbon and nutrients relative to ambient, unfertilized waters.…”
Section: Introductionmentioning
confidence: 99%
“…The Southern Ocean has been the site of several fertilization experiments as well, in the Atlantic [ Bakker et al , 2001], Indian [ Boyd et al , 2000; Boyd and Law , 2001; Gervais et al , 2002], and Pacific sectors [ Coale et al , 2004; Harvey et al , 2011]. All but the SOLAS Air‐Sea Gas Exchange Experiment (SAGE) [ Harvey et al , 2011] southeast of New Zealand showed strong increases in the primary productivity and biomass in mixed layer, and depletion of dissolved inorganic carbon and nutrients relative to ambient, unfertilized waters.…”
Section: Introductionmentioning
confidence: 99%